2023
DOI: 10.1186/s13021-023-00243-z
|View full text |Cite
|
Sign up to set email alerts
|

The impact of land cover change on the carbon stock of moist afromontane forests in the Majang Forest Biosphere Reserve

Semegnew Tadese,
Teshome Soromessa,
Abreham Berta Aneseye
et al.

Abstract: Backgorund Forest plays an important role in the global carbon cycle by sequestering carbon dioxide and thereby mitigating climate change. In this study, an attempt was made to investigate the effects of land use/land cover (LULC) change (1989–2017) on carbon stock and its economic values in tropical moist Afromontane forests of the Majang Forest Biosphere Reserve (MFBR), south-west Ethiopia. Systematic sampling was conducted to collect biomass and soil data from 140 plots in MFBR. The soil dat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 89 publications
0
1
0
Order By: Relevance
“…In the study area, a major conversion of forests to upland fields by 384.58 ha significantly depleted the aboveground carbon stocks in forests. Other studies have also revealed a decline in terrestrial carbon stocks due to LULC changes mainly attributed to the loss of vegetation cover [9,10,30,63]. The carbon storage and sequestration capacity decreased significantly over time as agricultural and urban land cover increased [64].…”
Section: The Changes In Lulc Effects On Aboveground Carbon Stocksmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study area, a major conversion of forests to upland fields by 384.58 ha significantly depleted the aboveground carbon stocks in forests. Other studies have also revealed a decline in terrestrial carbon stocks due to LULC changes mainly attributed to the loss of vegetation cover [9,10,30,63]. The carbon storage and sequestration capacity decreased significantly over time as agricultural and urban land cover increased [64].…”
Section: The Changes In Lulc Effects On Aboveground Carbon Stocksmentioning
confidence: 99%
“…The InVEST carbon storage and sequestration model performs better when studying and evaluating how climate change and LULC change affect carbon storage [28,29]. The InVEST model provides spatially explicit data (using spatial data), resulting in spatial and statistical data in terms of tons of carbon sequestered [30]. Such a model is effective in evaluating carbon storage in the landscape using carbon pool and LULC change data [31].…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars at home and abroad use the carbon storage plate in the InVEST model to predict carbon storage. For example, Tadese and Rajbanshi studied the relationship between land-use change and carbon storage in the Majang Forest Biosphere Reserve and the Konar catchment, India, respectively [11,12]. Xie [13], Wang [14], and Qing [15] estimated carbon storage and predicted different scenarios for the Huaihai Economic Zone, the Hubao and Yuyu urban agglomeration, and the Shihezi River Basin, respectively.…”
Section: Introductionmentioning
confidence: 99%